2016
DOI: 10.1212/wnl.0000000000002593
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationships among biomarkers for Alzheimer disease in the Adult Children Study

Abstract: CSF tau (Ptau181), PiB MCSUVR, and hippocampal volume were all longitudinally correlated with each other, whereas CSF Aβ42 was correlated only with PiB binding. Unlike the baseline values, the longitudinal change in CSF tau (Ptau181) and hippocampal volume were correlated with the longitudinal change in global cognition, validating the role of these biomarkers in Alzheimer disease prevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 37 publications
5
61
0
Order By: Relevance
“…This result further supports using baseline amyloid burden such as PiB PET as an important biomarker inclusion for secondary prevention trials in AD [1,3], and as a principle component of the newly proposed AD diagnostic criteria [28,29]. Also it has been reported that low baseline CSF Ab 42 leads to significant cognitive decline [7,30], this pattern was consistent in our results. In addition, the rate of change in CSF Ab 42 did not significantly predict the rate of cognitive decline, which is similar to the lack of correlation in previous reports [7].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result further supports using baseline amyloid burden such as PiB PET as an important biomarker inclusion for secondary prevention trials in AD [1,3], and as a principle component of the newly proposed AD diagnostic criteria [28,29]. Also it has been reported that low baseline CSF Ab 42 leads to significant cognitive decline [7,30], this pattern was consistent in our results. In addition, the rate of change in CSF Ab 42 did not significantly predict the rate of cognitive decline, which is similar to the lack of correlation in previous reports [7].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous reports [4][5][6], we found that higher cerebral amyloid deposition at baseline predicted longitudinal cognitive decline; however, the individual rate of change in amyloid did not. Xiong et al [7] previously evaluated the correlation between the change in amyloid deposition and the change in cognition in sporadic AD and concluded that the correlation was not significant, which is indirectly validated by our result in that the former does not predict the latter. For both cerebral amyloid deposition and CSF Ab 42 , the baseline value is more informative than the longitudinal change in predicting the cognitive decline.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A large portion of similar elderly adults as in this study has been reported to have "preclinical AD," 29 which indicates the absence of dementia symptoms in spite of AD neuropathological change in the brain. Accumulating biomarker evidence for a temporal cascade of changes in CSF biomarkers and PET amyloid uptakes 14,15 also supports the concept of preclinical AD with amyloid beta (Aβ) accumulation in the brain as a very early neuropathological process in AD. Neurofibrillary tangles and neuronal death, however, appear to begin during the preclinical phase of AD, but represent a closer event to the cognitive changes.…”
Section: Discussionmentioning
confidence: 82%
“…Different covariance matrices for the random effects and different residual variances were assumed between tracers. These models can handle missing, unbalanced, and unevenly spaced longitudinal data and have been used in previous studies of AD [30]. These analyses were done using Proc Mixed, SAS 9.4.…”
Section: Methodsmentioning
confidence: 99%